Women of the great barrier reef: Stories of gender and conservation - Foxwell-Norton, Kerrie; Anderson, Deb; Leitch, Anne M. (Queensland Review, 2021)
In the late 1970s, Carden Wallace was at the beginning of her lifelong exploration of the Great Barrier Reef - and indeed, reefs all over the world. For Wallace, who is now Emeritus Principal Scientist at Queensland Museum, the beginning of her Reef career coincided with the emergence of both feminist and environmental movements that meant her personal and professional lives would be entwined with a changing social, cultural and political milieu. In this article, we couple the story of Wallace's personal life and her arrival in coral science to identify the Reef as a gendered space ripe to explore both feminist and conservation politics. The article is part of a broader Women of the Reef project that supports a history of women's contribution to the care and conservation of the Reef since the 1960s. In amplifying the role of women in the story of the Reef, we find hope in the richness of detail offered by oral history to illuminate the ways discourse on the Reef and its women sits at the intersection of biography, culture, politics and place. In these stories, we recognise women's participation and leadership as critical to past challenges, and to current and future climate change action. By retelling modern Reef history through the experiences and achievements of women, we can develop new understandings of the Reef that disrupt the existing dominance of patriarchal and Western systems of knowledge and power that have led us to the brink of ecological collapse. © The Author(s), 2022.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; approches et analyses; australie; changements climatiques; environnement; histoire et politique; océanie; patriarcat; projet charge mentale; périodes historiques; régions géographiques; rôle des femmes dans la protection de la grande barrière de corail; systèmes d'oppressions; thématiques

Feeling beyond rules: Politicising the sociology of emotion and anger in feminist politics - Holmes, Mary (European Journal of Social Theory, 2004)
The part anger plays in motivating political action is frequently noted, but less is said about ways in which anger continues to be a part of how people do politics. This article critically assesses approaches to emotions that emphasize managing anger in accordance with ‘feeling rules’. It reflects on the utility of Marxist notions of conflict as the engine of change for the understanding of how anger operates in political life. This involves understanding the ambivalence of anger and its operation within particular power relations. Shifting sets of conventions have had some continuity in discouraging women in Western nations (particularly white and middle-class women) from showing anger. But clearly, women do get angry and feminists have drawn on anger in acting politically. New Zealand feminist writings from the ‘second wave’ are taken as illustrative of the common difficulties Western feminists faced in dealing with anger. These difficulties were due to trying to juggle social conventions about femininity, the political ideal of sisterhood, and the realities of dealing with other women in often new and experimental political processes. Anger could be personalized and hurtful, but in certain cases its expression was constructive in producing more respectful relations. Exploring these cases makes it clear how anger produces, and is produced by, relations with others.
Keywords: 1900-1999; 1970-1979; 1980-1989; colère; discipline; débat; militance; mouvements féministes; nouvelle-zélande; océanie; périodes historiques; rapports de pouvoir; ressource en ligne; régions géographiques; sciences humaines; sociologie; thématiques; émotions

Whose `Special Treatment'? Heterosexism and the Problems with Liberalism - Brickell, Chris (Sexualities, 2001)
This article examines the circulation of heterosexist positions within several recent New Zealand media texts. It argues that a recent form of discourse engages liberal language and assumptions in ways that support the privileged position of heterosexuality and the marginalization of homosexuality. The examples given highlight not only the tenor of some recent representations of homosexuality, but also some problems within liberalism. Most notable of these are liberalism's individualism and its failure to recognize the systemic nature of hierarchical power relationships and the constituting of lesbian and gay subjectivities within these relationships. These problems allow liberalism to play an active part in processes of domination and subordination.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; capitalisme; cours; discipline; discours médiatique; histoire; hétérosexisme; libéralisme; nouvelle-zélande; océanie; premier cycle; périodes historiques; rapports de domination; régions géographiques; sciences humaines; soc2014; sociologie; systèmes d'oppressions; thématiques; violences

The Quest for Modern Manhood: Masculine Stereotypes, Peer Culture and the Social Significance of Homophobia - Plummer, David C. (Journal of Adolescence, 2001)
This paper explores the use of homophobic terms by boys and young men and the meanings they invoke when using them. Highly detailed interviews were conducted with young men from diverse backgrounds about their own experiences while growing up and their observations of schools, teachers, family and peers. Homophobia was found to be more than a simple prejudice against homosexuals. Homophobic terms like “poofter” and “faggot” have a rich developmental history and play a central role in adolescent male peer-group dynamics. Homophobic terms come into currency in primary school. When this happens, words like poofter and faggot rarely have sexual connotations. Nevertheless, far from being indiscriminate terms of abuse, these terms tap a complex array of meanings that are precisely mapped in peer cultures, and boys quickly learn to avoid homophobia and to use it decisively and with great impact against others. Significantly, this early, very powerful use of homophobic terms occurs prior to puberty, prior to adult sexual identity and prior to knowing much, if anything, about homosexuality. An effect of this sequence is that early homophobic experiences may well provide a key reference point for comprehending forthcoming adult sexual identity formation (gay or not) because powerful homophobic codes are learned first.
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; approches et analyses; australie; cours; discipline; homophobie; hétérosexisme; masculinité; nouvelle-zélande; océanie; patriarcat; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; soc2014; sociologie; systèmes d'oppressions; thématiques; violences

Performances: l'art en action - Goldberg, RoseLee; Anderson, Laurie (Thames & Hudson, 1999)
Dresse un panorama complet des arts vivants depuis 1960 : happenings, théâtre et opéra d'avant-garde, danse contemporaine, art vidéo, installations multimédias. Yves Klein, Joseph Beuys, Robert Wilson, Tadeusz Kantor, Pina Bausch, Gilbert & George, Philippe Decouflé, entre autres, sont évoqués. L'ouvrage est illustré d'oeuvres européennes, américaines, japonaises et australiennes.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; amérique du nord; amériques; arts; asie; australie; corps; cours; discipline; europe; har4600; histoire de l'art; japon; océanie; premier cycle; périodes historiques; régions géographiques; thématiques; états-unis

Identity, emotion, and feminist collective action - Hercus, Cheryl (Gender and Society, 1999)
This article explores the relationship between identity, emotion, and feminist collective action. Based on interview research, the analysis confirms the central importance of anger in collective action and its particular significance for feminist identity and activism. As an emotion thought deviant for women, the anger inherent in feminist collective action frames created problems for participants in terms of relationships with partners, friends, and work colleagues. Participants performed emotion work to deal with negative responses to their feminist identity, but this depleted emotional energy and created stress. Participation in movement events provided much-needed emotional support and an outlet for deviant emotions.
Keywords: 1900-1999; 1990-1999; australie; colère; discipline; militance; océanie; organisations féministes; psychologie; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sociologie; thématiques; émotions; étude qualitative